PERENCANAAN GEOMETI JALAN REL KERETA API BUKITTINGGI-PAYAKUMBUH STA 94+675-STA 124+526 - Syamsuir, Elvi; Wahyuni, Fatma Ira; Siska, Sri Tria (Ensiklopedia of Journal, 2022)
West Sumatra Province is one of the provinces where the City and Regency have natural resources and many tourist objects. These cities and regencies have natural resources and tourist objects that have their respective advantages. Several cities from the many cities in West Sumatra that have a busy tourist attraction are the cities of Bukittinggi and Payakumbuh. In addition to having many tourist attractions, it also has abundant natural resources such as plantations, forestry, and industry. To visit and transport these resources, it must be supported by proper and adequate transportation facilities. Currently, the transportation used to transport goods and passengers uses roads, so it has the potential to cause problems both in terms of facilities and infrastructure and the emergence of congestion due to heavy traffic. Therefore, an alternative mode of transportation is needed to help reduce the burden of the highway, namely the mode of rail transportation for the smooth flow of distribution of goods and services, so it is felt that the Bukittinggi - Payakumbuh railway line is needed. This line is part of the route traversed by the Trans Sumatra Railway. This railway line is built or reactivated in order to reduce congestion that occurs at certain times. In the process of loading the Bukitinggi - Payakumbuh railway line, a methodology for collecting primary and secondary data, problem identification, literature study and analysis is needed. planning data in the form of design speed analysis, rail analysis and bearing analysis to be used. In this paper, the selection of the route, Geometric Planning, Railroad Construction Planning and at Km 15 is carried out. The selection of the route is based on the design speed of the train plan. Geometric planning using the Railways Management and Engineering method. Railroad construction refers to regulation PD-10 PJKA (1986). The results obtained from this paper are the planning of the railroad route as an alternative mode of transportation along ± 30 km from the City of Bukittinggi - Payakumbuh. So that it can be used as a comparison suggestion for the West Sumatra Provincial Government in building railroads in the future.